Bootleggers Beware! The Untold Story of Ordinances and Their Effect on Bootleggers and Local Law Enforcement in Kansas from 1915-1925 - Anderson, Nathan (Kansas State University, The Chapman Center for Rural Studies, 2018)
This project analyzes the role of local Kansas ordinances in enforcing larger, national laws; it also makes connections between ordinances and community values, showing that different geographic regions in the state had different levels of ordinance enforcement. The author presents case studies of several towns in Wabaunsee County, Harvey County, and the southeast Kansas counties of Crawford and Cherokee. This thorough study uses local ordinances, Kansas statutes, histories of Prohibition and bootlegging, newspaper articles, and local interviews.
Nathan Anderson, “Bootleggers Beware! The Untold Story of Ordinances and Their Effect on Bootleggers and Local Law Enforcement in Kansas from 1915-1925,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/254.
Keywords: Cherokee County; Crawford County; Kansas Politics; Prohibition; Walter Stubbs; Carry A. Nation